(untitled) (Comparative Professional Pedagogy, 2021)
The authors rely on the idea that the European experience of development and integration of non-formal education in the general education system shows the impact of the prevalence and value of education on the development of various social systems. In particular, human-centeredness as a basic principle of non-formal education is a condition for a fairer distribution of benefits as well as economic and social growth of the country. The connection between non-formal education and social work is presented through the development of the concept of "Learning Community". The idea of the concept is to increase the competitiveness of the local community by increasing educational opportunities and the corresponding status, economic, emotional, etc. growth. The dependence of economic growth of the community and the availability of educational services for the population is determined through the analysis of the data of the Human Development Index (HDI). Examples of the use of non-formal education for the implementation of social influences in European countries are given. The results of the analysis of indicators of the level of employment according to the monitoring report of the Ministry of Economic Development and Trade of Ukraine are presented. It is established that the lower the level of human education, the lower the percentage of its economic activity: the whole population 71.8 %; with full higher education 81.9 %; with vocational education  74.6 %; with complete general secondary education  58.6 %; with basic general secondary education  49.9 % with primary general education  9.4 %. The share of young people who do not work, study or acquire professional skills in the total number of people aged 15-24 is 14.5 %; 17.8 % of them are women, 11.3 % are men, 11.6 % are urban residents and 19.4 % are rural residents. Accordingly, the implementation of social policy aimed at economic activation of the population can be carried out through the introduction of non-formal education for people who due to age, family circumstances, health status, area of residence are socially excluded from community life. The potentials of non-formal education in the organization of social work with different categories of clients are formulated. It is proved that the use of non-formal education in social work as a tool of influence allows to provide the process of social support of resource-oriented approach, which relies on the strengths of clients through empowerment and consideration of needs.